Event2Ledger: Container traceability using Docker Swarm and consortium Hyperledger blockchain - Marques, Marco A.; Simplício Jr., Marcos A.; Miers, Charles Christian (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg), 2022)
Cloud computing employing container-based virtualization enables dynamic allocation of computational resources, providing scalability and fault tolerance, etc. However, this flexibility could imply a drawback: container environment monitoring is highly challenging due to the large flow of calls and (de)allocations. In this work, we present event2ledger, a blockchain-based solution that implements a distributed log with data sent by authorized and customized collectors to a permissioned consortium blockchain, responsible for ordering and storage in a distributed and auditable manner. A proof-of-concept is implemented with a Hyperledger Fabric consortium blockchain, composed and maintained by the scenario actors (i.e., Providers, Users, and Developers), which stores signed container life cycle events.